Payment of Wage under Minimum Wage for Abdi Dalem of Keraton in Daerah Istimewa Yogyakarta - Asri Wijayanti; Aniqotun Nafiah (Sociological Jurisprudence Journal, 2019)
The compensation for running a job is to get wages. There is one form of wage protection through minimum wage. The fact is there are still workers who have not earned a wage based on minimum wage after they run their jobs. One of them is the retainers of the court (Abdi Dalem) of Sultan palace of Yogyakarta. This study aims to analyze the validity of the wage system applied to the court servants who accept below the minimum wage. This study applies socio-legal approach. The result of this research is the Abdi Dalem get salaries in the form of â€œkecucaâ€ which amount is less than the minimum wage of Yogyakarta Province. Sultan Hamengkubuana X should be prosecuted for violation of Article 90 paragraph (2) jo. Article 187 of Law Number 13 Year 2003. The right to pursue of the courtiers has never been implemented because the working relationship between the courtiers and the Sultan is devotion. The sense of service is the soul of the agreement on which the working relationship is based. What has been agreed upon by the parties is binding as the law for the party making it (Article 1338 B.W. (Burgerlijkwetboek). The significance of this research is that the principle of local wisdom which is the basis of working relations can be unleashed. The contribution of this research is the emergence of an understanding that the employment relationship is not solely aimed at earning wages. A sense of tranquility after work becomes the choice of the destination of the courtiers to serve the Sultanate of Yogyakarta